Oral carbohydrate sensing enhances prefrontal cortex oxygenation, reduces perceived exertion, and improves high-intensity cycling performance: A randomized crossover trial - Seung-Bo Park; Kyungjin Oh; Geonwoo Yang; Taenam Kim; Jea Woog Lee; Hyung-Jin Jeon; Doug Hyun Han (PLoS ONE, 2026)
Purpose Carbohydrate mouth rinsing (CHO-MR) and music listening (MUS) are non-metabolic interventions proposed to attenuate cognitive and perceptual fatigue during exercise. However, their comparative effects on prefrontal cortical oxygenation, executive function, and perceived exertion during high-intensity endurance performance remain unclear. This study examined the effects of CHO-MR and MUS on dorsolateral prefrontal cortex (DLPFC) oxygenation, cognitive performance, perceived exertion, and cycling performance during a 4-km time trial (TT). Methods Eleven trained cyclists (7 men, 4 women) completed a randomized, single-blind, crossover trial under three conditions: CHO-MR, MUS (120 beats/min), and placebo mouth rinse (PLA). Bilateral DLPFC oxygenation was assessed using functional near-infrared spectroscopy at rest, during Stroop testing, post-intervention, and post-TT. Stroop performance, rating of perceived exertion (RPE); every 500 m, completion time, power output, heart rate, and blood lactate were measured. Outcomes were analyzed using generalized estimating equations adjusted for period, sequence, and first-order carryover effects with robust standard errors. Results CHO-MR increased bilateral DLPFC oxygenation compared with MUS and PLA at post-intervention and post-TT time points ( p < 0.05), with no differences at rest or baseline. Stroop performance was superior in CHO-MR relative to MUS and PLA following the TT ( p < 0.001), without between-condition differences at earlier assessments. RPE was lower in CHO-MR than PLA across all intervals ( p ≤ 0.01) and lower than MUS at mid-trial distances ( p < 0.05). CHO-MR resulted in faster completion times, greater mean power output, and higher mean speed compared with MUS and/or PLA ( p < 0.05), whereas peak power, heart rate, and blood lactate did not differ among conditions. Pooled change-score analyses demonstrated positive associations between bilateral ΔDLPFC oxygenation ( p < 0.001) and between ΔDLPFC oxygenation and ΔStroop performance ( p < 0.05). Conclusion CHO-MR enhances bilateral DLPFC oxygenation, preserves executive function, and reduces perceived exertion during high-intensity endurance exercise, translating into improved performance without detectable peripheral metabolic alterations. These findings support a central neurocognitive mechanism underlying the ergogenic effects of oral carbohydrate sensing. Trial registration ClinicalTrials.gov NCT 07099807